Hedging market risk using gold: A wavelet quintile correlation approach - Melan Sinaga; Agoestina Mappadang; Bayu Adi Nugroho (LPMP Imperium, 2024)
This research assesses gold's hedging and haven qualities against stock market fluctuations. This study uses the daily returns of three exchange-traded funds that best reflect the gold market and the stock markets of developed and emerging economies: iShares MSCI World (URTH), SPDR Gold (GLD), and SPDR S&P Emerging Markets (EDIV). The data set spans January 13, 2012, to December 29, 2023. For analytical purposes, this study estimates the dynamic correlation from the DCC-GARCH model and the newly constructed wavelet quantile correlations (WQC). According to WQC, gold has consistently been a short- and long-term haven for emerging markets during the COVID-19 pandemic and the Russia-Ukraine conflict. However, gold only shows the long-term safe-haven status for the developed markets. Further, this study shows that gold and stock correlations, both short- and long-term, do change with time. Lastly, this research suggests trading strategies based on a constant proportion approach. Public interest statements This study is useful for people to understand hedging methods and trading strategies for gold products